حماية العامل عند انتهاء علاقة العمل في التشريع الجزائري - زلاسي ،الأزهر; بلوم، صلاح الدين; نسيب، جمال (جامعة الوادي University of El Oued, 2024)
تعد حماية العامل عند إنتهاء العقد في القانون يعد موضوعا مهما، حيث تكمن أهميته في فهم الحماية التي يوفرها القانون للعامل عندما ينتهي عقده حيث تعد الحماية للعامل في فترة ما بعد إنتهاء العقد تجسيدا لمفهوم العدالة الاجتماعية وضمان إحترام حقوق العامل في المجتمع حيث يحظى العامل بالحماية بعد إنتهاء العقد من خلال تعديلات إجراءات قامت بها السلطات، عند انتهاء العقد يجب أن يحصل العامل على مجموعة من الحقوق والضمانات التي تكفل له الحماية القانونية والاجتماعية. Protecting the worker upon the expiration of the contract in the law is an important topic, as its importance lies in understanding the protection provided by the law to the worker when his contract ends, as the protection of the worker in the period after the expiration of the contract is an embodiment of the concept of social justice and ensuring respect for the worker's rights in society, as the worker enjoys protection after the expiration of the contract through amendments to the procedures made by the authorities. Upon the expiration of the contract, the worker must obtain a set of rights and guarantees that guarantee him legal and social protection.
ماستر اداري